Dynamics of Phosphorus Sorption and Desorption in Ultisols Ameliorated with Humic Substances from Potential Ameliorants - Amsar Maulana; Dewi Rezki; Irwan Darfis; Zahlul Ikhsan; Herviyanti Herviyanti (CIB Nusantara, 2025)
Ultisols have a very high P sorption capacity, which limits the availability of P to plants. Therefore, it is necessary to understand the P sorption-desorption mechanism after humic substances (HS) amelioration to improve fertilizer efficiency and land productivity. This study has examined the complexity of phosphorus fixation and the potential of HS in modifying the surface charge of Ultisols. This study used the batch equilibrium method and the Freundlich and Langmuir isotherm model approaches. Meanwhile, the surface charge characteristics of Ultisols, amended with humic substances (HS) from various potential ameliorants (control, HS-chicken manure, HS-black soldier fly, HS-wet decanter solid, and HS-peat), were evaluated using a completely randomized design with three replications. The HS from potential ameliorants significantly increases pH, PZC, electrical conductivity (EC), mineral and organic matter composition, CEC, and reduces potential redox (Eh), thereby increasing the soil's negative charge and buffering capacity. The HS—wet decanter solid and chicken manure were most effective, as they were proven to remove Al-exchange to unmeasurable levels through strong complexation between Al³⁺ and carboxylate and phenolic groups. The HS—wet decanter solid and chicken manure also drastically reduce P sorption and increase desorption through ligand competition and blocking of Al/Fe reactive sites, which resulted in increased P availability up to >600 mg kg-1 P2O5 at a concentration of 1000 mg L-1 P or 2290 mg kg⁻¹ P₂O₅ or 6.37g SP-36 per liter or 6.37 kg SP-36 per hectare for an application volume of 1,000 liters per hectare.